Bronchoalveolar Lavage Complements Transbronchial Cryobiopsy Diagnosis in Diffuse Interstitial Lung Diseases. Issue 1 (January 2022) - Serra, Candela; Torrego, Alfons; Pajares, Virginia; Millan-Billi, Paloma; Barril, Silvia; Alonso, Ana; Navarro, Marta; Lopez, Laura; Franquet, Tomas; Castillo, Diego
Abstract : Background: Bronchoalveolar lavage (BAL) is a technique classically used for the study of diffuse interstitial lung diseases (DILDs). Given the recent advances in the diagnosis of DILD by transbronchial cryobiopsy (TBCB), it is relevant to assess what BAL can contribute to TBCB. Patients and Methods: This is a retrospective descriptive study that included patients with DILD who, between 2013 and 2017, underwent BAL and TBCB in the same bronchoscopy intervention. We evaluated the complementary information provided by BAL to TBCB that facilitated the diagnosis by a multidisciplinary committee. Epidemiological, clinical, and functional variables and high-resolution chest tomography findings were recorded, along with complications associated with the procedures. Results: A total of 60 patients were included. TBCB, conditioned by the underlying radiologic pattern, provided diagnostic information in 75% of cases. BAL provided complementary information that supported the diagnosis and treatment in 22% of cases. Differential BAL findings were related to microbiology, cell count, and immunology. Regarding the safety of the procedure, 47% of the patients experienced complications, although none were serious. Conclusion: BAL findings contribute to TBCB findings in the diagnosis of DILDs, with no serious complications associated with their combined use.